2024
DOI: 10.1038/s41467-024-46268-x
|View full text |Cite
|
Sign up to set email alerts
|

Mating harassment may boost the effectiveness of the sterile insect technique for Aedes mosquitoes

Dongjing Zhang,
Hamidou Maiga,
Yongjun Li
et al.

Abstract: The sterile insect technique is based on the overflooding of a target population with released sterile males inducing sterility in the wild female population. It has proven to be effective against several insect pest species of agricultural and veterinary importance and is under development for Aedes mosquitoes. Here, we show that the release of sterile males at high sterile male to wild female ratios may also impact the target female population through mating harassment. Under laboratory conditions, male to f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…An estimation of the size of the wild mosquito population is necessary for the determination of the appropriate quantity of sterile males to be released for controlling the population effectively, which should be at least more than 10 times higher than that of the natural population size to see a quick suppression [19,31,55]. The current study showed a wild mosquito population density ranging from 95 to 232 males/ha (mean 163 males/ha), which shows a high density of wild mosquitoes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…An estimation of the size of the wild mosquito population is necessary for the determination of the appropriate quantity of sterile males to be released for controlling the population effectively, which should be at least more than 10 times higher than that of the natural population size to see a quick suppression [19,31,55]. The current study showed a wild mosquito population density ranging from 95 to 232 males/ha (mean 163 males/ha), which shows a high density of wild mosquitoes.…”
Section: Discussionmentioning
confidence: 61%
“…The current study showed a wild mosquito population density ranging from 95 to 232 males/ha (mean 163 males/ha), which shows a high density of wild mosquitoes. Considering the results of this study and other studies [19,31,55], release rates of more than 163 males/ha can be considered for future trials in Sri Lanka. The significant difference in wild male population sizes between the first and second release series could be attributed to several factors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…B. dorsalis is a significant pest, with a global distribution and rapid reproduction, and it causes substantial damage to fruit and vegetable production [ 36 ]. Recently, the SIT has been applied to the control of pests such as Aedes aegypti and Ceratitis capitata [ 37 , 38 ]. The successful application of the SIT is based on the elucidation of the reproductive developmental rules and the identification of reproduction-related or sex-related genes, especially the gonad-specific genes.…”
Section: Discussionmentioning
confidence: 99%